Utilization of Facebook as a Promotional Media for Mount Rinjani National Park - Saleh, M. Surya; Nugraha, Rizki Nurul (Westscience Press, 2024)
Facebook is one of the largest social media platforms in the world, by offering various features that can be used for the promotion of products or services from a company. The purpose of this study is to identify and analyze promotional strategies carried out by Gunung Rinjani National Park through the use of Facebook social media. This type of research is qualitative, with qualitative descriptive analysis methods. Data collection was carried out through direct observation and taking data from Facebook social media accounts belonging to Mount Rinjani National Park, the data taken included photos and videos posted on Facebook. The results showed that Gunung Rinjani National Park implements effective and efficient promotion strategies through the use of social media such as Facebook. This destination implements various promotional strategies such as, sharing interesting visual content, holding competitions, organizing educational activities, and disseminating information